The transformation of host communities and the formation and evolution of ethnic residential enclaves in Spain - Sabater, Albert; Galeano, Juan; Domingo, Andreu (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
Residential segregation remains one of the most visibledivision between different population groups and inherent inmany modern societies. In Spain, the study of changes in the geographical distribution of the recently immigrated population has emerged as a key area to inform empirical debates about the nature of the new settlements in the various Spanish municipalities which have become destinations of international migration. The main objective of this research is to analyse the transformation of host communities (those that are mainly inhabited by people born in Spain) and the formation and evolution of ethnic residential enclaves in Spain. For this purpose, this investigation has employed a time series (2000-2010) of detailed population data disaggregated by sex, age and country of birth of residents in all census tracts that constitute the administrative map of Spain.
Keywords: Host communities; Ethnic enclaves; Spatial homogeneity- heterogeneity; Demography; Spain